Program Bimbingan Sebaya Pendekatan Mentoring Halaqah dalam Membantu Penyesuaian Diri Mahasantri - Noviza, Neni; Nuraida, Nuraida; Helia, Helia; Muzayanah, Muzayanah (Bulletin of Counseling and Psychotherapy, 2022)
The purpose of this study was to determine the existing programs in the Ma'had Al-Jami'ah UIN Raden Fatah Palembang, and formulating a peer guidance program with a halaqah mentoring approach in helping students adjust themselves to the activities at Ma'had Al-Jami'ah UIN Raden Fatah Palembang. This research is descriptive qualitative research. The data collection technique used was interview, observation, and documentation. The research subjects were students who had problems in adjusting to the activities at Ma'had Al-Jami'ah UIN Raden Fatah Palembang, batch 2019/2020, totaling 6 people and Maha'd administrators. The data analysis technique used was data reduction, data presentation, drawing conclusions and verification. The results of this study show that programs in Ma'had Al-Jami'ah are religious knowledge (taqrir mufradat, learning community worship, muhadassah, tahfizul Qur'an, taddabur Al-Qur'an, learning fahmul fiqh, reading the book Hidayatus Salikin, learning Arabic, muhadoroh, recitation of the Qur'an, majlis dzikir and calligraphy) and general science (scientific writing, learning English, sports, marawis and dance). The adjustment of mahasantri to the activities in Mahad is categorized as low in the aspect of not being able to control excessive emotions, being unable to overcome psychological mechanisms, not having rational self-judgment and direction, not having the ability to learn and not being objective and realistic.